Hydrogen Sulfide Alleviates Aluminum Toxicity via Decreasing Apoplast and Symplast Al Contents in Rice - Zhu, Chun Q.; Zhang, Jun H.; Sun, Li M.; Zhu, Lian F.; Abliz, Buhailiqem; Hu, Wen J.; Zhong, Chu; Bai, Zhi G.; Sajid, Hussain; Cao, Xiao C.; Jin, Qian Y. (Frontiers in Plant Science, 2018)
Hydrogen sulfide (H2S) plays a vital role in Al3+ stress resistance in plants, but the underlying mechanism is unclear. In the present study, pretreatment with 2 μM of the H2S donor NaHS significantly alleviated the inhibition of root elongation caused by Al toxicity in rice roots, which was accompanied by a decrease in Al contents in root tips under 50 μM Al3+ treatment. NaHS pretreatment decreased the negative charge in cell walls by reducing the activity of pectin methylesterase and decreasing the pectin and hemicellulose contents in rice roots. This treatment also masked Al-binding sites in the cell wall by upregulating the expression of OsSATR1 and OsSTAR2 in roots and reduced Al binding in the cell wall by stimulating the expression of the citrate acid exudation gene OsFRDL4 and increasing the secretion of citrate acid. In addition, NaHS pretreatment decreased the symplasmic Al content by downregulating the expression of OsNRAT1, and increasing the translocation of cytoplasmic Al to the vacuole via upregulating the expression of OsALS1. The increment of antioxidant enzyme (SOD, APX, CAT, and POD) activity with NaHS pretreatment significantly decreased the MDA and H2O2 content in rice roots, thereby reducing the damage of Al3+ toxicity on membrane integrity in rice. H2S exhibits crosstalk with nitric oxide (NO) in response to Al toxicity, and through reducing NO content in root tips to alleviate Al toxicity. Together, this study establishes that H2S alleviates Al toxicity by decreasing the Al content in the apoplast and symplast of rice roots.